Five new cardenolides transformed from oleandrin and nerigoside by Alternaria eureka 1E1BL1 and Phaeosphaeria sp. 1E4CS-1 and their cytotoxic activities. (February 2021) - Karakoyun, Çiğdem; Küçüksolak, Melis; Bilgi, Eyüp; Doğan, Gamze; Çömlekçi, Yiğit Ege; Bedir, Erdal
Graphical abstract: Highlights: First fungal biotransformation study on oleandrin and nerigoside was performed. Structures of five new metabolites were established. Biotransformation reactions were mainly monooxygenation and desacetylation. Oleandrin and monohydroxylated metabolites exhibited potent cytotoxic activity. Oleandrose sugar and 16- O -acetyl group are important features for potent cytotoxicity. Abstract: Biotransformation of oleandrin (1 ) and nerigoside (2 ) by endophytic fungi; Alternaria eureka 1E1BL1 and Phaeospheria sp. 1E4CS-1, has led to the isolation of five new metabolites (3, 5, 6, 7 and 8 ) together with a known compound (4 ). The structures of the biotransformation products were elucidated by 1D-, 2D NMR and HR-MS. Phaeospheria sp. mainly provided monooxygenation reactions on the A and B rings, whereas A. eureka afforded both monooxygenated and desacetylated derivatives of the substrates. Cytotoxic activity of the compounds was tested against a non-cancerous (HEK-293) and four cancer (PANC-1, MIA PaCa-2, DU 145 and A549) cell lines by MTT cell viability assay. All compounds were less cytotoxic than oleandrin, which had IC50 values ranging between 2.7 and 41.9 nM. Two of the monohydroxylated metabolites, viz. 7( β )-hydroxy oleandrin (3 ) and 1( β )-hydroxy oleandrin (7 ), were also potent with IC50 values from 18.45 to 39.0 nM, while desacetylated + monohydroxylated, or dihydroxylated products had much lower cytotoxicity. Additionally, the lesser activity of 2 and its metabolite (6 ) possessing diginose as sugar residue inferred that oleandrose moiety is important for the toxicity of oleandrin as well as hydrophobicity of the steroid core.